Potensi Dan Pengelompokan Usaha Pertanian Di Kabupaten Tolikara Provinsi Papua - Bembok, Nomiles; Rengkung, Leonardus Ricky; Montolalu, Maya Hendrietta (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to reduce or simplify variables using Principal Component Analysis, and group sub-districts in Tolikara Regency using Cluster Analysis. The data taken in the study is secondary data from the official publication of the Central Bureau of Statistics with agricultural production data in this study are 46 sub-districts in Tolikara district in 2023, while the variables in this study are 13 agricultural production results. The results of this study formed 3 principal components which are linear combinations of the original constituent variables and are able to explain 74.197% of the variation of the 13 variables. The formation of 3 groups or clusters of 46 sub-districts using the average lingkage cluster analysis method.